Vacuum-assisted closure for chest wall reconstruction infection caused by Streptococcus mitis after surgery of lung cancer: a case report - Nozomu Motono; Takaki Mizoguchi; Masahito Ishikawa; Shun Iwai; Yoshihito Iijima; Hidetaka Uramoto (Surgical Case Reports, 2024)
Abstract Background Among a cohort of patients who underwent chest wall resection and reconstruction by rigid prosthesis, 6% required removal of the prosthesis, and in 80% of these cases the indication for prosthesis removal was infection. Although artificial prosthesis removal is the primary approach in such cases of infection, the usefulness of vacuum-assisted closure (VAC) has also been reported. Case presentation A 64-year-old man with diabetes mellitus underwent right middle and lower lobectomy with chest wall (3rd to 5th rib) resection and lymph node dissection because of lung squamous cell carcinoma. The chest wall defect was reconstructed by an expanded polytetrafluoroethylene (PTFE) sheet. Three months after surgery, the patient developed an abscess in the chest wall around the PTFE sheet. We performed debridement and switched to VAC therapy 2 weeks after starting continuous drainage of the abscess in the chest wall. The space around the PTFE sheet gradually decreased, and formation of wound granulation progressed. We performed wound closure 6 weeks after starting VAC therapy, and the patient was discharged 67 days after hospitalization. Conclusions We experienced a case of chest wall reconstruction infection after surgery for non-small cell lung cancer that was successfully treated by VAC therapy without removal of the prosthesis. Although removal of an infectious artificial prosthesis can be avoided by application of VAC therapy, perioperative management to prevent surgical site infection is considered essential.